DEVELOPMENT OF GUIDED INQUIRY-BASED STUDENT WORKSHEETS ON ELEMENT, COMPOUND, AND MIXTURE MATERIALS - Putriyani, Putriyani; Masriani, Masriani; Lestari, Ira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
In science learning activities,learning objectives can be achieved if students are active in learning activities.The form of student activity in learning can be seen from the skills of asking questions and finding (lookingfor) answers that originate from their curiosity.Therefore, teaching materials are needed that can make students active, as a tool in the learning process and can be used as a learning resource. One of them is the Student Worksheet (LKPD). However, the LKPD circulating in school semphasizes more on questions and filling inquestions without explaining how the process of obtaining answers to these questions. In addition, the LKPD used looks monotonous, unattractive, and difficult to understand so that students are less motivated to study and understand the contents of the LKPD. Therefore, it is necessary to develop LKPD which aims to find out the stages in making guided inquiry based LKPD to determine the feasibility of LKPD to be used as teaching materials, and to determine student responses to guided inquiry-based LKPD on elements,compounds and mixtures in class VIISMP. The form of researchuse disresearch and development (R&D) which adopts the 4D development model (Define,design,develop,dessiminate) by Thiagarajan. The subject to this study was a guided inquiry based LKPD on elements, compounds, and mixtures which were testedon 24 students of class VII at junior high school 12 Pontianak with high, medium, and low abilities. The data collection instruments used were the feasibility assessment and student response questionnaires.Theresult so data `processing show that the developed LKPD is suitable for use in learning in terms of content feasibility with a percentage of 82%, 90% presentation, 77% language86% graphics. The result so student response trials to the product obtained student responses with a score of 82,06% with very high interpretations.